The Need for Accessible Health Education - Laughlin, Michael K.; Benes, Sarah; Sherlock-Shangraw, Rebecca (Journal of Physical Education, Recreation and Dance, 2026)
Health education in preschool through 12th grade is an essential component of a well-rounded education and can positively impact student health and well-being. All school-age students deserve access to high-quality, effective health education. However, students with disabilities may not be receiving the health education they are entitled to for many reasons, including that there is not a clearly defined understanding of health education for students with disabilities. Working from the perspective that health education is both a social justice imperative and an important component of students’ “well-rounded education” under the Every Student Succeeds Act of 2015, this article is a call to action and brings attention to this area of need. It is framed around three critical questions: (1) Why do students with disabilities deserve access to health education? (2) How should health education for students with disabilities be conceptualized? (3) Where does accessible health education go from here? By articulating these questions and providing initial thoughts to spur further discussion and action, this article encourages invested partners and collaborators to address this critical need so that students with disabilities can meaningfully access the same high-quality health education opportunities as their peers. © 2026 SHAPE America.
Keywords: dept.hms

Testing Multiple Delivery Methods of the Virtual Exercise Games for Youth with T1D Peer Intervention: Protocol Development and Feasibility - Ash, Garrett I.; Nam, Soohyun; Mak, Selene S.; Stults-Kolehmainen, Matthew; Haughton, Adrian D.; Turek, Carolyn; Baker, Julien S.; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth G.; et al. (Hormone Research in Paediatrics, 2026)
Abstract – Introduction: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. Methods: The program included 6 versions: study 1 (1.1–1.4) included an active video game, and study 2 (2.1–2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. Results: Seventeen adolescents (median age 15.4 [IQR 14.6–16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%–11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min–90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = −1.12, 90% CI: [−1.78, −0.48]). Conclusions: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention’s impact on engagement with physical activity, glycemic outcomes, and quality of life. © 2026 S. Karger AG, Basel
Keywords: Diabetes; Peer support; Physical activity; Type 1; Video games; dept.hms

Introducing “Preservice Pipeline”—Why This Column, Why Now - Knipe, Bob (Journal of Physical Education, Recreation and Dance, 2026)
Future professionals learn to lead through a variety of professional opportunities, and it is time that JOPERD provides a forum dedicated to their development and an opportunity for them to lead as authors and coauthors. This article describes the new Preservice Pipeline column and how to submit articles. © 2026 SHAPE America.
Keywords: dept.hms

Testing multiple delivery methods of the virtual exercise games for youth with T1D peer intervention: protocol development and feasibility - Ash, Garrett; Nam, Soohyun; Mak, Selene; Stults-Kolehmainen, Matthew; Haughton, Adrian; Turek, Carolyn; Baker, Julien; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth; et al. (Hormone Research in Paediatrics, 2026)
INTRODUCTION: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. METHODS: The program included 6 versions: study 1 (1.1-1.4) included an active video game, and study 2 (2.1-2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. RESULTS: Seventeen adolescents (median age 15.4 [IQR 14.6-16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%-11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min-90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = -1.12, 90% CI: [-1.78, -0.48]). CONCLUSIONS: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention's impact on engagement with physical activity, glycemic outcomes, and quality of life.
Keywords: Glycemic; Physical activity; Program evaluation; Protocol (science); Quality (philosophy); Quality of life (healthcare); dept.hms

The effect of high dose creatine supplementation on thermoregulatory adaptation during a standard heat acclimation protocol - Martin, David; Thornton, Staci; Langan, Seam; Navarro, John; Brewer, Gabrielle; Szymanski, Michael; Huggins, Robert; Lunn, William; Rodriguez, Nancy; Casa, Douglas; Lee, Elaine (Medicine & Science in Sports & Exercise, 2025)
Keywords: Acclimatization; Analysis of variance; Core temperature; Creatine; Dehydration; Heat stress; Rectal temperature; Thermoregulation; dept.hms

College community–based physical activity support at a public university during the COVID-19 pandemic: retrospective longitudinal analysis of intra- versus interpersonal components for uptake and outcome association - Ash, Garrett; Mak, Selene; Haughton, Adrian; Augustine, Madilyn; Bodurtha, Phillip; Axtell, Robert; Borsari, Beatrice; Liu, Jason; Lou, Shaoke; Xin, Xin; Fucito, Lisa; Jeon, Sangchoon; et al. (JMIR mhealth and uhealth, 2025)
Background College students are vulnerable to setting long-term trajectories of low physical activity (PA) but are reachable via mobile health fitness tracking (eg, mobile health step counting) and interpersonal support tailored to the college community. However, no studies have statistically isolated the appeal and influence of these intra- and interpersonal components in college-based PA interventions. Objective This study retrospectively examined a college-based PA promotion program at a northeast US public university during the COVID-19 pandemic to (1) test the impact of student status on the use of intervention components and (2) determine whether such use was associated with successful retention and goal achievement in the program. Methods The university used a commercial platform for a 30-day PA promotion program during April 2021 with intrapersonal (step-tracker syncing, education, self-monitoring, and motivational messaging) and interpersonal (friend interactions and team games) components. App use was operationalized as intrapersonal (frequency of opening app, education, and self-monitoring) and interpersonal (friends made in-app and team affiliation and size). Results Campus-wide emails elicited sign-up by 156 undergraduate students, 57 graduate students, and 126 faculty and staff members. Objective 1 yielded the following results: undergraduates used the app less frequently (median 0.8, IQR 0.4-1.7 times per day) than other groups (graduate students: median 1.4, IQR 0.7-2.7 times per day; P=.01; faculty: median 1.3, IQR 0.7-2.7 times per day, H2=14.5; P=.001) but made the same number of friends (median 1-2) and teammates (median 8-9; P=.77 for friends and P=.93 for teammates). Objective 2 yielded the following results: most participants (313/335, 93.4%; 95% CI 90%-96%) were retained for the first 7 days, but by 30 days, retention dropped, most notably for undergraduate students (82/154, 53.2%; 95% CI 45%-61%), followed by graduate students (39/56, 70%; 95% CI 56%-81%) and faculty and staff (93/125, 74.4%; 95% CI 66%-82%; χ22=12.6; P<.001). Retention was associated with app engagement frequency (model hazard ratio 0.56, 95% CI 0.43-0.72; P<.001) and affiliation with a team having high median app engagement and a large size (intracluster correlation coefficient 0.064, 95% CI 0.001-0.164, P=.05). Meeting a daily step goal was associated with app engagement frequency (β=.72, SE=0.21; P=.001), number of friends (β=.40, SE 0.20; P=.04), and an initial motive of maintaining or increasing (rather than starting) PA (β=.99, SE=0.21; P<.001). Conclusions College students, compared with faculty and staff, used the app less frequently, used the app for a shorter duration before abandonment, and met the step goal on fewer days. Engagement with the program was associated with longer retention and better PA outcomes, which were critically modified by the interpersonal engagement. These findings suggest that college students using virtual PA support during times of physical isolation could benefit from more tailored implementation strategies (eg, timed prompts and team reassignments).
Keywords: Computer science; Coronavirus disease 2019 (COVID-19); Demography; Disease; Gerontology; Infectious disease (medical specialty); Internal medicine; Medicine; Preprint; Sociology; dept.hms

National Trends in Athletic Training Service Provision in U.S. High Schools: A Five-Year Longitudinal Assessment - Kim, D; Eason, Christianne; Grubb, Joseph; Casa, Douglas; Coleman, Kelly; Filep, Erica; Huggins, Robert (Current Sports Medicine Reports, 2026)
Keywords: Athletes; Athletic training; Sports medicine; Trainer; Training (meteorology); dept.hms

Comparison Of Measures Of Arterial Stiffness Between Women With And Without Polycystic Ovarian Syndrome - Lecher, Madison; Rupp, Kristie; Latchman, Peter (Medicine & Science in Sports & Exercise, 2025)
Keywords: Arterial stiffness; Blood pressure; Body mass index; Etiology; Polycystic ovary; Pulse wave velocity; dept.hms

Similar Relative Energy Deficiency In Sport (REDs) Variables In Men And Women NCAA Distance Runners - Bryan, J.; Rupp, Kristie; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Basal metabolic rate; Bone mineral; Doubly labeled water; Dual energy; Energy expenditure; Energy metabolism; Fat free mass; Fat mass; Physical activity; dept.hms

Assessing Asymmetry In Collegiate Sprint And Intermediate Hurdlers - Gregory, Robert; Dale, Hunter (Medicine & Science in Sports & Exercise, 2025)
Keywords: Asymmetry; Ground reaction force; Impulse (physics); Jump; Plyometrics; Sprint; dept.hms

Effect Of Creatine Monohydrate Supplementation On VO2 Kinetics In Aerobically Fit Adults - Raymond, Emerson; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Blood lactate; Creatine; Crossover study; Heart rate; Lactate threshold; Percentile; Treadmill; VO2 max; Ventilatory threshold; dept.hms

Body Composition Evaluation During The Competitive Season Of An NCAA Division II Men's Soccer Team - Lunn, William; Axtell, Robert (Medicine & Science in Sports & Exercise, 2025)
Keywords: Athletes; Body fat percentage; Competitive athletes; Composition (language); Division (mathematics); Fat mass; Lean body mass; Team sport; dept.hms

936 - Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: dept.hms

Forgotten Learners: High School Transition Students With Disabilities - Laughlin, Michael K. (Journal of Physical Education, Recreation and Dance, 2026)
Because physical literacy and activity are not emphasized in special education as they are in physical education or adapted physical education (PE/APE), this editorial explores two important questions: Do high school transition students receive PE/APE programming? And are PE/APE teachers introduced or exposed to transition services at any point in their teacher training?. © 2026 SHAPE America.
Keywords: dept.hms

Reply - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott; Benes, Sarah (The Journal of Pediatrics, 2025)
Keywords: dept.hms

Remote Lesson Study as Continuing Professional Development for Physical Education Teachers - Colburn, Jeffrey; Knipe, Robert; Doherty, Brooke; Stephenson, Rachyl; Hamilton, Xiaofen (Journal of Teaching in Physical Education, 2026)
Purpose: This study investigated experiences of physical education teachers (PETs) participating in online remote andragogy-based lesson study (AbLS) during a pandemic. Method: Five PETs participated in this phenomenological case study. Seventeen online AbLS collaborative meetings took place via Zoom software. Three rounds of semistructured interviews were conducted and analyzed using collaborative qualitative analysis. Results: Three themes emerged: (a) AbLS facilitated depth of learning, increasing professional and individual growth; (b) AbLS structure influenced experience; and (c) the professional community of AbLS supported a natural adult learning (andragogical) environment. Discussion/Conclusion: Remote AbLS presented benefits for these PETs beyond professional learning that prior continuing professional development had not, including a sense of community, belonging, and professional worth. AbLS may have implications for research in perceived mattering and continuing professional development facilitation for PETs. Remote AbLS may bolster PETs in challenging local learning communities. © 2026 Human Kinetics, Inc.
Keywords: andragogy; dept.hms; marginalization; professional learning; remote communities

Healthy Futures for Young Women With Obesity: A Mixed Methods Study - Rupp, Kristie; Bryan, JohnM.; Abel-Berei, Catherine (American Journal of Health Promotion, 2025)
Keywords: Focus group; Health promotion; Intervention (counseling); Mental health; Obesity; Perception; Physical activity; Psychological intervention; Psychosocial; dept.hms; health behavior; weight bias; weight stigma; women’s health

Availability of School-Based Sexual and Reproductive Health Services - Zhong, Anthony; Szlosek, Donald; Gao, Chloe; Dang, Nhu; Benes, Sarah (American Journal of Preventive Medicine, 2025)
Keywords: Health services; MEDLINE; Public health; Reproductive health; Sexual behavior; dept.hms

Athletic Training Services Trends Between Public and Private High Schools: A 5-Year Retrospective Analysis - Kim, Donghyeon; Defino, Amir; Eason, Christianne; Casa, Douglas; Yoo, Chaeyeon; Yoshihara, Ayami; Coleman, Kelly; Filep, Erica; Huggins, Robert (Journal of Athletic Training, 2025)
Context Access to athletic trainers (ATs) in high schools is crucial for student-athlete (SA) safety. Although most high schools in the United States have access to athletic training services (ATS), no authors have longitudinally compared ATS trends between public (PUB) and private (PVT) school sectors. Objective To compare ATS trends between PUB and PVT schools from the 2018–2019 through 2022–2023 academic years. Design Longitudinal cross-sectional study. Setting Online survey. Main Outcome Measure(s) High school responses to the Athletic Training Locations and Services survey from all 50 US states and the District of Columbia were queried from the 2018–2019 to 2022–2023 academic years. Average numbers of SAs ( SAs ), sports ( Sports ), full-time ATs ( FtATs ), part-time ATs ( PtATs ), and the sum of full-time and part-time ATs ( ATs ), along with the average weekly contracted hours ( CHrs ) and actual hours ( AHrs ) per school, and ratios of SAs : ATs , Sports : ATs , CHrs : SAs , CHrs : Sports , AHrs : SAs , and AHrs : Sports were examined to track ATS trends over 5 years and compare PUB vs PVT schools. Results Public schools had higher SAs and Sports vs PVT schools (both P < .001). Private schools had higher ATs , CHrs , and AHrs than PUB schools (all P < .050). Ratios of SAs : ATs and Sports : ATs were higher in PUB schools, whereas CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports were higher in PVT schools (all P < .050). From 2018–2019 to 2022–2023, PUB schools increased Sports and Sports : ATs ; PVT schools increased SAs , Sports , ATs , and SAs : ATs (all P < .050). Over the years, PUB schools decreased CHrs : Sports and AHrs : Sports ; PVT decreased CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports . FtATs increased in both sectors, whereas PtATs decreased in only PVT schools. Conclusions Overall, ATS were more extensively provided in PVT schools, based on ATs and ATS hours. Both sectors increased FtATs , which is encouraging. However, as SAs and Sports increased, ATS provided per SA and sport declined.
Keywords: Athletes; Athletic training; Context (archaeology); MEDLINE; Private sector; Training (meteorology); athletes; dept.hms; safety; sports; student health services

Educational Programming to Prevent Violence in Schools in the United States: An Analysis of School Health Profiles - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott; Benes, Sarah (The Journal of Pediatrics, 2025)
This repeated, cross-sectional study examined trends in the availability of school-based programming to prevent violence in middle and high schools across the United States from 2008 to 2020. Overall, violence prevention programming increased in respondent schools throughout the study period. However, important gaps remain, with lingering state-level disparities.
Keywords: Human factors and ergonomics; Injury prevention; Occupational safety and health; Poison control; Respondent; Suicide prevention; adolescent health; dept.hms; health education; school violence prevention; teacher training; youth violence prevention

Position Statements for Advocacy: Does Using Physical Activity as Punishment Make Students Leave Physical Education Wanting to Hide or Seek? - Paulson, Lisa; Knipe, Robert (Strategies, 2025)
This article explains how to use and apply the SHAPE America position statement “Physical Activity Should Not Be Used as Punishment and/or Behavior Management” in one’s own teaching and as an advocacy tool. © 2025 SHAPE America.
Keywords: dept.hms

Adolescent Concern for Body Weight and Engagement in Unhealthy Weight Control Behaviors - McCoy, Stephanie; Bryan, Jessica; Rupp, Kristie (American Journal of Health Promotion, 2025)
Keywords: Binge eating; Body mass index; Body weight; Clinical psychology; Demography; Disordered eating; Eating disorders; Environmental health; Gerontology; Internal medicine; Logistic regression; Medicine; Obesity; Odds; Odds ratio; Pill; dept.hms; eating behaviors; obesity; psychosocial health

Is Your Physical Education Adapted or Adaptive? - Laughlin, Michael K. (Journal of Physical Education, Recreation and Dance, 2025)
For decades, adapted physical education advocates have passionately engaged in a debate over two adjectives: adapted vs. adaptive. This article explores the reasons why one is preferred over the other and why it matters, especially to students with disabilities. © 2025 SHAPE America.
Keywords: dept.hms

An Exergames Program for Adolescents With Type 1 Diabetes: Qualitative Study of Acceptability - Mak, Selene S.; Nally, Laura M.; Montoya, Juanita; Marrero, Rebecca; DeJonckheere, Melissa; Joiner, Kevin L.; Nam, Soohyun; Ash, Garrett I. (JMIR Diabetes, 2025)
Background: Numerous barriers to moderate to vigorous physical activity exist for youths with type 1 diabetes (T1D). The virtual exercise games for youth with T1D (ExerT1D) intervention implement synchronous support of moderate to vigorous physical activity including T1D peers and role models. Objective: This study aims to understand the acceptability of this intervention to participants. Methods: We conducted postprogram, semistructured, televideo interviews with participating youths to elicit perspectives on the acceptability of the intervention and experience with the program. Two coders independently reviewed and analyzed each transcript using a coding scheme developed inductively by senior researchers. Discrepancies were resolved by team discussion, and multiple codes were grouped together to produce 4 main thematic areas. Results: All 15 participants provided interviews (aged 14-19 years; 2 nonbinary, 6 females; median hemoglobin A1c level of 7.8% (IQR 7.4%-11.2%), 5 with a hemoglobin A1c level of ≥10%). Qualitative data revealed four themes: (1) motivation to engage in physical activity (PA)—improving their physical capabilities and stabilizing glucose levels were cited as motivation for PA and challenges of living with T1D were cited as PA barriers; (2) experience with and motivation to manage diabetes while engaging in PA—participants provided details of accommodating the inherent uncertainty or limitations of PA with diabetes and sometimes preparing for PA involved psychological and motivational adjustments while some relayed feelings of avoidance; (3) peer support encouraged engagement with the intervention—participants appreciated the peer aspects of components of ExerT1D and participants’ reflections of the facilitated group experience highlight many benefits of a small-group virtual program; and (4) improvements in PA and diabetes self-management efficacy—all participants credited the program with improving or at least raising awareness of T1D management skills. Conclusions: Our virtual PA intervention using an active video game and discussion component provided adolescents with T1D the confidence and peer support to engage in PA, improved awareness of diabetes-specific tasks to prepare for exercise, and improved understanding of the effect of PA on glucose levels. Engaging youths with a virtual video game intervention is a viable approach to overcome barriers to PA for adolescents with T1D. Trial Registration: ClinicalTrials.gov NCT05163912; https://clinicaltrials.gov/ct2/show/NCT05163912
Company: JMIR Diabetes Distributor: JMIR Diabetes Institution: JMIR Diabetes Label: JMIR Diabetes
Keywords: Computer science; Diabetes mellitus; Medicine; Preprint; Psychology; Qualitative research; Sociology; Type 2 diabetes; World Wide Web; dept.hms; peer-reviewed

Integrating edTPA into Physical Education Teacher Education: Teacher Educators’ Perceptions and Experiences in Preparing Teacher Candidates - Olsen, Edward B.; Wyant, James D.; Tsuda, Emi; Laughlin, Michael K.; Baxter, Deborah S. (Journal of Teaching in Physical Education, 2024)
Purpose: In the United States, 15 states maintain policies and 25 states represent some level of edTPA affiliation. This study investigated how the edTPA was integrated and aligned into different physical education teacher education (PETE) programs in New Jersey. It also sought to understand teacher educators’ perceptions and experiences in preparing teacher candidates for the edTPA. Methods: This study utilized three data sources: semistructured interviews (n = 4), one focus group interview (n = 1), and documents (n = 17). Data analysis reflected a conventional approach toward qualitative content analysis. Results: In analyzing the data, four themes were established: (a) benefits and drawbacks of edTPA in PETE, (b) goals and success of edTPA in PETE, (c) integrating edTPA into PETE—macro- and microperspectives, and (d) analytic insights into edTPA and future recommendations. Discussion/Conclusion: In states requiring the edTPA, early exposure, scaffolding, curriculum mapping, and a shared mission and vision are critical. In states not requiring the edTPA, programs may want to consider indicators of performance, such as artifacts, reports, elements of the edTPA, university-based assessments, or a portfolio. Regardless of the type of assessment, “a” performance-based assessment may help to determine teacher candidates’ ability to plan, instruct, assess, and reflect.
Keywords: dept.hms; faculty; peer-reviewed; performance-based assessments; preservice teachers

Acute arterial stiffness responses to on-ball kneeling and sitting: Effects of exercise fragmentation and exercise order - Xiao, Yaru; Chen, Wei; Latchman, Peter; Zhou, Zhixiong; Zhu, Weili (European Journal of Applied Physiology, 2025)
Keywords: Arterial stiffness; Ball balance; Blood pressure; Cardio-ankle vascular index; Cardiology; Exercise physiology; Fragmentation; Human physiology; Internal medicine; Kneeling; Medicine; Moderate exercise; Order; Physical exercise; Physical medicine and rehabilitation; Physical therapy; Posture; Sitting; Sports medicine; dept.hms; peer-reviewed

Sex Differences in Response to a 12-Week Resistance Training Exercise Intervention After Cardiac Surgery: A Proof-of-Concept Intervention Trial - Safdar, Basmah; Jarman, Angela; Madsen, Tracy; DeLamielleure, Lauren; Zhou, Bin; Axtell, Robert; Geirsson, Arnar; Mangi, Abeel (Clinical Therapeutics, 2025)
Keywords: Cardiac rehabilitation (CR); Cardiac surgery; Cardiovascular disease (CVD); Intervention (counseling); Medicine; Nursing; Physical therapy; Randomized controlled trial; Resistance strength training; Resistance training; Safety and feasibility; Sex differences; Surgery; dept.hms; peer-reviewed

Fostering cultural competence: Exploring client perception in a health coaching intervention among college students - Oh, Seungbin; Benes, Sarah; Yan, Zi (Nursing & Health Sciences, 2024)
Health coaching could be an innovative approach to develop student coaches' cultural competence (CC) among future health professionals. The current mix-method study design explored the impact of an 8-week peer health coaching intervention among college students on CC, from both student health coaches (i.e., students majored in health sciences who completed health coaching training and acted as health coach) and student clients' perspective. Nine student coaches and 24 student clients participated in the study. The quantitative analysis showed an increase in the clients' perceived level of coaches' CC between the pre- and posttest. The qualitative analysis revealed three themes, including varying levels of awareness, respectful and culturally responsive coaching, and cultural connection. Implications and recommendations for educators and researchers are discussed.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/nhs.13077
Keywords: cultural competence; cultural humility; dept.hms; health coaching; mixed-method design; peer-reviewed

Exercise Prescription - Older Adults - Axtell, Robert; Robertson, M. I. (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

Muscular Strength Assessment - Axtell, Robert (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

Spinal cord injury management policies in high school sports as reported by athletic administrators - Scarneo-Miller, Samantha E.; Swartz, Erik E.; Register-Mihalik, Johna K.; Coleman, Kelly A.; Emrich, Christina M.; DiStefano, Lindsay J. (Translational Journal of the American College of Sports Medicine, 2024)
Introduction/Purpose Athletic administrators (AA) in U.S. high schools are uniquely positioned to provide guidance and endorsement for the prevention and management of common sport-related catastrophic injuries, such as the development of a spinal cord injury management (SCIM) policy. The purpose of this project was to evaluate AA’s knowledge of comprehensive SCIM policies in U.S. high schools. Secondarily, we aimed to investigate the factors, facilitators, and barriers to the development and adoption of comprehensive policies. Methods An online questionnaire was distributed to 6423 AA working in U.S.-based high school athletics, with 366 included in the final data analysis. The questionnaire evaluated AA’s knowledge of comprehensive SCIM policies addressing components of adoption, documentation, and communication. The questionnaire was developed based on the 2002 “National Athletic Trainers’ Association Position Statement: Acute Management of the Cervical Spine-Injured Athlete.” The questionnaire also inquired about facilitators and barriers to developing and adopting comprehensive policies. Proportions were calculated for policy adoption, and independent-samples t-tests evaluated the influence of athletic training services on comprehensive SCIM policies. Results About half of AA (49.2%, n = 180/366) reported having all recommended components of a written SCIM policy. AA who had access to an athletic trainer (yes = 62.9%, no = 18.1%, unknown = 19%) were more likely to have a comprehensive SCIM policy compared with those without access (80.6% vs 19.4%, χ21 = 7.091, P = 0.008, prevalence ratio = 1.24, 95% confidence interval = 1.03–1.50). The most commonly reported facilitator (49.9%) was “having a medical professional at the school,” and the main barrier (30.2%) was “my school would need more information, resources, assistance, etc.” Conclusions The findings identify areas for improvement in supporting the health and safety of children in high school participating in interscholastic athletics. Future dissemination and implementation research should develop strategies tailored to individual school community and need to improve SCIM policy adoption and implementation.
Keywords: dept.hms

The impact of an 8-week wellness peer coaching program on physical activity among college students: 1338 - Peacock, Jessica; Yan, Zi; Bowling, April; Benes, Sarah (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Marathon and ultra-endurance performance - Lunn, William R. (Medicine & Science in Sports & Exercise, 2023)
Num Pages: 1
Keywords: dept.hms; peer-reviewed

Cannabidiol supplementation alleviates anxiety, mitigates pain, extends endurance, and facilitates greater exercise exertion: 277 - Lunn, William R.; Axtell, Robert S. III; Venard, Anna; Bodurtha, Phillip; Brunello, Greta; Bukowski, Zachary (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Prevalence of physical activity, sleep, and screen-time in youth before and during the covid-19 pandemic: 1735 - Rupp, Kristie; Friel, Ciaran P. (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Evaluating the Usability of the Wellness School Assessment Tool Whole School, Whole Community, Whole Child (WellSAT WSCC): A School Wellness Policy Assessment Tool - Connolly, K.; Koslouski, J.B.; Chafouleas, S.M.; Schwartz, M.B.; Edmondson, B.; Briesch, A.M. (Journal of School Health, 2023)
BACKGROUND: Adoption of the Whole School, Whole Community, Whole Child (WSCC) model has been slowed by a lack of available tools to support implementation. The Wellness School Assessment Tool (WellSAT) WSCC is an online assessment tool that allows schools to evaluate the alignment of their policies with the WSCC model. This study assesses the usability of the WellSAT WSCC. METHODS: Using a convergent mixed methods design, we collected qualitative and quantitative data from 5 school-based participants with roles in development and evaluation of policy. Participants explored the platform while engaging in a think-aloud procedure and scored a sample policy using the platform. They also completed the System Usability Scale and responded to open-ended questions about the usability of the platform. RESULTS: Participants rated the WellSAT WSCC as an above-average user experience, but data suggested several areas for improvement, including improved instructions, enhanced visual design of the platform, and guidance for subsequent policy changes. CONCLUSION: The WellSAT WSCC provides an above-average user experience but can be improved to increase user experience. These improvements increase the potential for greater use to facilitate integration of the WSCC model into school policy. © 2023, American School Health Association.
Keywords: WSCC model; WellSAT WSCC; dept.hms; peer-reviewed; school health; school policy; whole child

Do maturation, anthropometrics and leg muscle qualities influence repeated change of direction performance in adolescent boys and girls? - Giuriato, M.; Pellino, V.C.; Lovecchio, N.; Codella, R.; Vandoni, M.; Talpey, S. (Biology of Sport, 2023)
The ability to change direction rapidly is a key fitness quality especially in invasive sports where young players perform approximately 300 changes of direction in a game. There is currently limited understanding of how anthropometric characteristics and maturation status influence change of direction ability in adolescent. Therefore, the purpose of this investigation is to assess the influence of anthropometrics and maturation status on change of direction ability in young people. The study involved 706 adolescents (367 girls) aged 14-19-year-old attending the same high school in Northern Italy. Stature, body mass, seated height and leg length were measured to determine the anthropometrics and maturation status of the participants. Repeated change of direction ability (10 × 5 m shuttle run test), lower limb power and muscle strength were evaluated using field tests from the Eurofit test battery. Maturity offset was calculated separately for boys and girls, in accord with the equation proposed by Mirwald. Preliminary analysis with 10 × 5 m as a dependent variable and sex and PHV as a fixed factor, suggests a significant difference between sex (p < 0.001; d = 0.35) but not with PHV (p = 0.986; d = 0.000) and interaction PHV × sex (p = 0.836; d = 0.000). Our results suggested that repeated change of direction performance was influenced by anthropometrics, maturation and muscle qualities in adolescent boys and girls. © 2023 Institute of Sport. All rights reserved.
Keywords: Adolescent; Change of Direction; Eurofit Test; Peak Height Velocity; Speed; dept.hms; peer-reviewed

Physical Activity, Sleep, and Screen Time in Children and Adolescents Before and During the COVID-19 Pandemic: An Analysis of the 2019-2020 National Survey of Children’s Health - Friel, C.P.; Diaz, K.M.; Rupp, K. (American Journal of Health Promotion, 2023)
The COVID-19 pandemic led to unprecedented changes in people’s lifestyles across the United States, but the extent to which the pandemic affected health behaviors of children and adolescents (i.e., physical activity, screen-time, and sleep) is not well understood. These behaviors hold particular significance because of their association with health outcomes. Purpose: The purpose of this study was to examine whether engagement in health behaviors changed from pre-pandemic (2019) to during the pandemic (2020). Methods: The combined 2019-2020 National Survey of Children’s Health (NSCH) was used to inform this study. The NSCH is an annual survey designed to provide national estimates of key indicators of childhood health and well-being. Physical activity (number of days/week with >60 min of activity), screen-time (hours/day of TV viewing and computer use), and sleep (hours/day) were assessed by parental report. Adjusted binomial and multinomial logistic regression models were used to determine the association between survey year and health behaviors. Results: Children and adolescents were 36% more likely to be physically inactive in 2020 compared to 2019. Additionally, children and adolescents were 14% more likely to meet sleep guidelines and 39% less likely to meet screen-time guidelines in 2020 compared to 2019, independent of age, sex, race/ethnicity, and poverty level. Children (6-13 year) and adolescents (14-17 years) were 10% and 15% less likely to get below the recommended amount of sleep in 2020 compared to 2019, respectively. Conclusion: Prevalence of meeting sleep guidelines increased among children and adolescents in 2020 but decreased for physical activity and screen-time. Initiatives targeting activity and screen-time may be urgently needed. Whether rates of these health behaviors return to pre-pandemic levels over the next few years should be closely assessed. © The Author(s) 2023.
Keywords: adolescents; children; dept.hms; health behaviors; peer-reviewed; physical activity; screen time; sedentary behavior; sleep

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
1 citations (Crossref) [2023-10-31]
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Understanding health behaviors, weight perceptions, and body appreciation of young adult women engaged in the body positivity movement - Rupp, Kristie; McCoy, Stephanie M. (Women's Health Issues, 2023)
Background The body positivity movement on social media is thought to foster body appreciation, but pervasive societal concern persists about the body positivity movement and the body image, health behaviors, and “normalization of obesity” of young adult women. Purpose This study explored the relationship between engagement in the body positivity movement on social media and weight status, body appreciation, body dissatisfaction, and the health behaviors of intuitive eating and physical activity in young adult women (18–35 years). Methods Participants (N = 521; ∼64% engaged in body positivity content on social media) were recruited using Qualtrics online panels for this cross-sectional survey during February 2021. Outcomes included weight status, weight consideration, weight perception, body appreciation, body dissatisfaction, physical activity, and intuitive eating. Logistic and linear regression models adjusted for age, race, ethnicity, education level, and household income were used to assess the association between engagement in the body positivity movement and specified outcomes. Results Engagement in body positivity content was associated with greater body dissatisfaction (β = 2.33, t(519) = 2.90 p = .017), body appreciation (β = 0.26, t(519) = 2.90 p = .004), and greater likelihood of reporting high amounts of physical activity (odds ratio = 2.28; p < .05) relative to nonengaged peers; these associations remained significant after further adjustment for weight status. Body positivity was not associated with weight status, weight perception, or intuitive eating. Conclusions Engagement in the body positivity movement is associated with higher body dissatisfaction and body appreciation in young adult women, which suggests they may be drawn to and engage in the body positivity movement as a protective or coping mechanism for body dissatisfaction.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Exertional heat illness: adoption of policies and influencing contextual factors as reported by athletic administrators - Scarneo-Miller, Samantha E.; Adams, William M.; Coleman, Kelly A.; Lopez, Rebecca M. (Sports Health, 2023)
Background:Little is known about the adoption by athletic administrators (AAs) of exertional heat illness (EHI) policies, and the corresponding facilitators and barriers of such policies within high school athletics. This study describes the adoption of comprehensive EHI policies by high school AAs and explores factors influencing EHI policy adoption.Hypothesis:We hypothesized that <50% of AAs would report adoption of an EHI policy, and that the most common facilitator would be access to an athletic trainer (AT), whereas the most common barrier would be financial limitations.Study Design:Cross-sectional.Level of Evidence:Level 4.Methods:A total of 466 AAs (82.4% male; age, 48 ± 9 years) completed a validated online survey to assess EHI prevention and treatment policy adoption (11 components), as well as facilitators and barriers to policy implementation. Access to athletic training services was ascertained by matching the participants? zip codes with the Athletic Training Locations and Services Project. Policy adoption, facilitators, and barriers data are presented as summary statistics (proportions, interquartile range (IQR)). A Welch t test evaluated the association between access to athletic training services and EHI policy adoption.Results:Of the AAs surveyed, 77.9% (n = 363) reported adopting a written EHI policy. The median of EHI policy components adopted was 5 (IQR = 1,7), with only 5.6% (n = 26) of AAs reporting adoption of all policy components. AAs who had access to an AT (P = 0.04) were more likely to adopt a greater number of EHI-related policies, compared with those without access to an AT. An AT employed at the school was the most frequently reported facilitator (36.9%).Conclusion:Most AAs reported having written EHI policy components, and access to an AT resulted in a more comprehensive policy.Clinical Relevance:Employment of an AT within high school athletics may serve as a vital component in facilitating the adoption of comprehensive EHI policies.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

An 8-week peer health coaching intervention among college students: a pilot randomized study - Yan, Zi; Peacock, Jessica; Cohen, Juliana F. W.; Kurdziel, Laura; Benes, Sarah; Oh, Seungbin; Bowling, April (Nutrients, 2023)
This study explored the effects of an 8-week peer coaching program on physical activity (PA), diet, sleep, social isolation, and mental health among college students in the United States. A total of 52 college students were recruited and randomized to the coaching (n = 28) or the control group (n = 24). The coaching group met with a trained peer health coach once a week for 8 weeks focusing on self-selected wellness domains. Coaching techniques included reflective listening, motivational interviews, and goal setting. The control group received a wellness handbook. PA, self-efficacy for eating healthy foods, quality of sleep, social isolation, positive affect and well-being, anxiety, and cognitive function were measured. No interaction effects between time and group were significant for the overall intervention group (all p > 0.05), while the main effects of group difference on moderate PA and total PA were significant (p < 0.05). Goal-specific analysis showed that, compared to the control group, those who had a PA goal significantly increased vigorous PA Metabolic Equivalent of Task (METs) (p < 0.05). The vigorous METs for the PA goal group increased from 1013.33 (SD = 1055.12) to 1578.67 (SD = 1354.09); the control group decreased from 1012.94 (SD = 1322.943) to 682.11 (SD = 754.89); having a stress goal significantly predicted a higher post-coaching positive affect and well-being, controlling the pre-score and other demographic factors: B = 0.37 and p < 0.05. Peer coaching showed a promising effect on improving PA and positive affect and well-being among college students.
1 citations (Crossref) [2023-10-31] Number: 5
Keywords: dept.hms; diet; mental health; peer-reviewed; physical activity; positive affect; sleep; stress

Perception of moderate-intensity physical activity by onset of obesity: A randomized crossover trial - Rupp, Kristie; Stewart, Andrea L.; Friel, Ciarán P. (Clinical Obesity, 2022)
Moderate-intensity physical activity is recommended for inactive adults with overweight/obesity (OW/OB). The objective of this study is to determine if differences exist in the selection of moderate intensity between inactive adults with juvenile-onset (JO) and adult-onset (AO) OW/OB. Participants (JO = 18, AO = 20) were stratified by onset and completed two separate 20-minute moderate-intensity exercise sessions on a treadmill and cycle ergometer (randomized order). Multiple linear regression was used to determine whether exercise intensity (average METS, % age-predicted HRmax), self-reported pleasure or exertion differed by onset, controlling for age and gender. On the treadmill, JO and AO participants selected an average intensity of (mean [SD]) 3.5 (0.9) and 3.7 (0.9) METS, and 64.0 (7.7) and 64.9 (7.5) % of age-predicted HRmax, respectively. On the cycle, JO and AO participants selected an average intensity of 3.3 (0.9) and 3.3 (1.0) METS, and 65.2 (8.8) and 60.7 (7.2) % of age-predicted HRmax. After adjustment, participant intensity selection did not significantly differ by obesity onset when walking or cycling. There were no significant differences in pleasure or perceived exertion by onset, however, perception of exertion was on the high-end of moderate for both the cycle (13.0, 12.5) and treadmill (12.0, 12.1), in JO and AO participants, respectively. Perception of moderate intensity did not differ by obesity onset. Self-selected intensity was at the low end of moderate for walking and cycling.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/cob.12492
Keywords: dept.hms; exercise enjoyment; overweight; peer-reviewed; perceived exertion; self-selected intensity; weight loss

Discriminative ability of lower limb strength and power measures in lacrosse athletes - Talpey, Scott W.; Axtell, Robert; Gardner, Elizabeth; Maloney, Maggie; Newman, Thomas; Cordone, Jason; O’Grady, Mathew (International Journal of Sports Medicine, 2023)
The objective of this investigation was to compare isokinetic strength, countermovement jump and drop jump variables between high-contributors and low-contributors within NCAA Division I Men’s and Women’s lacrosse athletes. Men’s (N=36) and Women’s (N=30) NCAA Division I lacrosse athletes completed strength testing of the quadriceps and hamstring across three speeds (60°·s−1, 180°·s−1, 300°·s−1), countermovement and drop jumps. To determine the discriminative ability of select lower-limb strength and power characteristics participants were categorized as high-contributors (Males N=18, age=20.3±0.4 yrs, height=183.9±5.5 cm, mass=90.8±5.8 kg; Females N=15, age=20.8±0.8 yrs, height=169.3±6.7 cm, mass=64.1±7.2 kg) or low-contributors (Males N=18, age=19.5±0.2 yrs, height=184.1±5.6 cm; mass=87.9±8.1 kg; Females N=15, age=19.7±0.2 yrs, height=169.8±7.0 cm, mass=62.9±7.7 kg ) based upon the number of games the participants competed in during the regular season. Within the male cohort, moderate significant (p−1 (d=0.69) and peak power in countermovement jump (d=0.68). Within the women’s cohort a large (d=0.87) significant difference (p−1. Hamstring strength and lower-limb power are important strength measures for lacrosse performance and should be prioritized in training prescription for lacrosse athletes.
0 citations (Crossref) [2023-10-31]
Keywords: Key words countermovement jump; dept.hms; drop jump; female athlete; peer-reviewed; performance

Physical Activity, Sports Participation, and Psychosocial Health in Adolescents With Hearing Loss - DeLuca, Zara Waldman; Rupp, Kristie (Journal of Adolescent Health, 2022)
Purpose This study examined the association between hearing status (i.e., adolescents with and without hearing loss) and physical activity and sports participation. Secondarily, we explored the association between physical activity and sports participation and psychosocial outcomes among adolescents with hearing loss. Methods Analyses included 29,034 adolescents (52.1% male, 13.8 ± 2.3 (M ± SD) years) from the combined 2018–2019 National Survey of Children's Health. Adolescents were grouped by hearing status. Adjusted logistic regression models assessed physical activity level (i.e., 0, 1–3, 4–6, and 7 days/week) and sports participation (i.e., participation in sports within the past 12 months) by hearing status. Secondary analyses examined associations between physical activity and sports participation with psychosocial outcomes among adolescents with hearing loss adjusting for relevant confounders. Results Relative to their hearing peers, adolescents with hearing loss (n = 359) were 40% [adjusted odds ratio (AOR), 0.60; 95% confidence interval (CI), 0.44, 0.81], 43% [AOR, 0.57; 95% CI, 0.41, 0.80], and 33% [AOR, 0.67; 95% CI, 0.47, 0.95] less likely to engage in 1–3 days/week of physical activity, 4–6 days/week of physical activity, and meet physical activity guidelines, respectively. Further, adolescents with hearing loss were 31% [AOR, 0.69; 95% CI, 0.55, 0.85] less likely to participate in sports. Sports participation, but not physical activity, was associated with a significant reduction in the likelihood of experiencing adverse psychosocial outcomes among adolescents with hearing loss (p's < .05). Discussion Sports participation, but not physical activity, was associated with attenuated likelihood of experiencing adverse psychosocial outcomes in adolescents with hearing loss, suggesting unique characteristics of sports participation confer protection of psychosocial health. Increasing access to and reducing barriers to engagement in sports should be prioritized to improve psychosocial health in adolescents with hearing loss.
4 citations (Crossref) [2023-10-31]
Keywords: Hearing loss; Physical activity; Psychosocial health; Sports participation; dept.cmd; dept.hms; peer-reviewed

Combining MRI and cognitive evaluation to classify concussion in university athletes - Ly, Monica T.; Scarneo-Miller, Samantha E.; Lepley, Adam S.; Coleman, Kelly; Hirschhorn, Rebecca; Yeargin, Susan; Casa, Douglas J.; Chen, Chi-Ming (Brain Imaging and Behavior, 2022)
Current methods of concussion assessment lack the objectivity and reliability to detect neurological injury. This multi-site study uses combinations of neuroimaging (diffusion tensor imaging and resting state functional MRI) and cognitive measures to train algorithms to detect the presence of concussion in university athletes. Athletes (29 concussed, 48 controls) completed symptom reports, brief cognitive evaluation, and MRI within 72 h of injury. Hierarchical linear regression compared groups on cognitive and neuroimaging measures while controlling for sex and data collection site. Logistic regression and support vector machine models were trained using cognitive and neuroimaging measures and evaluated for overall accuracy, sensitivity, and specificity. Concussed athletes reported greater symptoms than controls (∆R2 = 0.32, p < .001), and performed worse on tests of concentration (∆R2 = 0.07, p < .05) and delayed memory (∆R2 = 0.17, p < .001). Concussed athletes showed lower functional connectivity within the frontoparietal and primary visual networks (p < .05), but did not differ on mean diffusivity and fractional anisotropy. Of the cognitive measures, classifiers trained using delayed memory yielded the best performance with overall accuracy of 71%, though sensitivity was poor at 46%. Of the neuroimaging measures, classifiers trained using mean diffusivity yielded similar accuracy. Combining cognitive measures with mean diffusivity increased overall accuracy to 74% and sensitivity to 64%, comparable to the sensitivity of symptom report. Trained algorithms incorporating both MRI and cognitive performance variables can reliably detect common neurobiological sequelae of acute concussion. The integration of multi-modal data can serve as an objective, reliable tool in the assessment and diagnosis of concussion.
0 citations (Crossref) [2023-10-31]
Keywords: Classification; Concussion; Diffusion tensor imaging (DTI); Mild traumatic brain injury (mTBI); Resting state functional MRI; dept.hms; peer-reviewed

Before-school physical activity program's impact on social and emotional learning - Goh, T.L.; Leong, C.H.; Fede, M.; Ciotto, C. (Journal of School Health, 2022)
BACKGROUND: Despite the positive impact of social and emotional learning (SEL) on the emotional well-being of children, literature on physical activity engagement and SEL among this population has been limited. Therefore, the purpose of this study was to examine whether school students' SEL would improve after participation in a before-school physical activity program. METHODS: A total of 138 fourth and sixth grade students from 1 elementary school and 1 middle school participated in this study. Seventy-five students participated in the before-school physical activity program, while 63 students were in the control group. The physical education teachers implemented the program 3 days per week, for 3 weeks. The participants completed a 10-question adapted Devereux Student Strengths Assessment-Mini before and after the program. Repeated measures ANOVA was run to determine the effects of the program on SEL competence. RESULTS: The fourth and sixth grade students who participated in the program reported a 7 and 10% improvement in pre- versus post-intervention SEL competence, respectively. Students in the control group reported no change in their SEL competence. CONCLUSION: Considering the benefits of a before-school physical activity program on students' SEL, stakeholders should consider including more physical activity programming within school policies. © 2022 American School Health Association.
1 citations (Crossref) [2023-10-31] tex.author_keywords: elementary school; middle school; physical education; social-emotional competence tex.document_type: Article tex.source: Scopus
Keywords: dept.hms; peer-reviewed

Heart rate recovery, central systolic pressure, and augmentation index in young healthy individuals - Latchman, P.L.; Yang, Q.; Kong, L.; Zhang, H.; Sebagisha, J.; De Meersman, R.E. (Vascular Health and Risk Management, 2022)
Purpose: Measuring heart rate recovery (HRR) holds valuable cardiovascular information and requires minimal technical skill and cost. Understanding the associations between HRR and more robust cardiovascular indicators, such as central systolic blood pressure (CSBP), can provide valuable cardiovascular information with less involvement. CSBP is a strong predictor of certain cardiovascular diseases. The study aims to examine the association between measures of HRR and CSBP and the augmentation index (AIx) in a group of young, healthy individuals and based on sex. Participants and Methods: One-hundred and seven participants (men – 55, women – 52) were measured for HRR at one minute (HRR1) and two minutes (HRR2) after maximum oxygen consumption (VO2max) testing, CSBP, and the AIx at a heart rate of 75 beats∙min−1 (AIx@75). Results: The Pearson correlation indicated no association between HRR1, HRR2, and CSBP in men and women combined: r = 0.06, P = 0.53; r = 0.05, P = 0.59, respectively, or based on sex: men = r = 0.01, P = 0.95; r = 0.04, P = 0.79, respectively, and women = r = −0.05, P = 0.75; r = −0.09, P = 0.52, respectively. However, there were associations between HRR1 and AIx@75 in men and women combined: r = −0.37, P < 0.001, and based on sex: men = r = −0.31, P = 0.02, and women = r = −0.38, P < 0.01. Conclusion: Measures of HRR were not associated with CSBP in a combined group of young men and women or based on sex. Most measures of HRR, especially those established by parasympathetic nervous activity, were associated with lower AIx@75. Though measures of HRR might be good indicators of cardiovascular disease, they might not be good indicators of CSBP in young, healthy individuals. © 2022 Latchman et al.
3 citations (Crossref) [2023-10-31] tex.author_keywords: Augmentation index; Central blood pressure; Central systolic blood pressure; Heart rate recovery; Sex tex.document_type: Article tex.pubmed_id: 35173435 tex.source: Scopus
Keywords: Article; Blood Pressure; Cardiovascular Diseases; Cardiovascular System; Female; Heart Rate; Humans; Male; adult; augmentation index; blood pressure; cardiovascular disease; cardiovascular parameters; cardiovascular system; central systolic pressure; cholinergic system; controlled study; dept.hms; diastolic blood pressure; female; heart rate; heart rate recovery; heart rate variability; human; human experiment; male; maximal oxygen uptake; normal human; peer-reviewed; predictive value; sex difference; systolic blood pressure; young adult

Changes in health behaviors associated with weight gain by weight classification during the COVID-19 pandemic. - Rupp, Kristie; Friel, Ciarán P (American journal of health promotion : AJHP, 2021)
Purpose: To determine whether perceived changes (i.e. perception of engagement during the pandemic relative to pre-pandemic) in specific health behaviors differ by weight status (i.e. healthy weight, overweight, obese). Design: Cross-sectional. Recruitment took place between June-August 2020, via social media posts and Qualtrics online panels. Setting: Participants completed the survey online through the Qualtrics platform. Sample: Analyses included N = 502 participants (≥18 years); 45.2% healthy weight (n = 227), 28.5% overweight (n = 143), and 26.3% obese (n = 132). Measures: Study-specific survey items included questions about demographics and perceived changes in health behaviors. Analysis: Logistic regression models, adjusted for age, race, ethnicity, gender, education, and COVID-19 diagnosis, assessed the odds of perceiving changes in health behaviors considered a risk for weight gain. Results: Participants with obesity, but not overweight, were significantly more likely to report deleterious changes to health behaviors compared to healthy weight peers, including: (1) decreased fruit/vegetable consumption [adjusted odds ratio (AOR) = 1.92; 95% confidence interval (CI): (1.13, 3.26)]; (2) increased processed food consumption [AOR = 1.85; 95%CI: (1.15, 3.00)]; (3) increased caloric intake [AOR = 1.66; 95% CI: (1.06, 2.61)]; (4) decreased physical activity [AOR = 2.07; 95%CI: (1.31, 3.28)]; and (5) deterioration in sleep quality [AOR = 2.07; 95%CI: (1.32, 3.25)]. Conclusion: Our findings suggest that adults with obesity may be at greater risk for unhealthy behaviors during a period of prolonged social distancing, potentially exacerbating the obesity epidemic. © The Author(s) 2021.
4 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34098761/ ; https://europepmc.org/article/MED/34098761 ; http://journals.sagepub.com/doi/10.1177/08901171211022958 ; https://www.ncbi.nlm.nih.gov/pubmed/34098761 ;
Keywords: COVID-19; COVID-19 Testing; Cross-Sectional Studies; Health Behavior; Humans; Pandemics; SARS-CoV-2; Sleep Quality; Weight Gain; body weight gain; cross-sectional study; dept.hms; health behavior; human; pandemic; peer-reviewed; sleep quality

Athletic training employment in secondary schools by geographic setting and school size within the United States. - Suzuki-Yamanaka, Miwako; Huggins, Robert A.; Armstrong, Kirk J.; Coleman, Kelly A.; Casa, Douglas J.; Kaneoka, Koji (Journal of athletic training, 2021)
Context: The Athletic Training Locations and Services (ATLAS) Annual Report suggested that athletic trainer (AT) employment status differed based on geographic locale. However, the influence of geographic locale and school size on AT employment is unknown. Objective: To determine if differences existed in the odds of having AT services by locale for public and private schools and by student enrollment for public schools. Design: Cross-sectional study. Setting: Public and private secondary schools with athletics programs. Patients or Other Participants: Data from 20 078 US public and private secondary schools were obtained. Main Outcome Measures(s): Data were collected by the ATLAS Project. Athletic trainer employment status, locale (city, suburban, town, or rural) for public and private schools, and school size category (large, moderate, medium, or small) only for public schools were obtained. The employment status of ATs was examined for each category using odds ratios. Logistic regression analysis produced a prediction model. Results: Of the 19 918 public and private schools with available AT employment status and locale, suburban schools had the highest access to AT services (80.1%) with increased odds compared with rural schools (odds ratio = 3.55 [95% CI = 3.28, 3.85]). Of 15 850 public schools with known AT employment status and student enrollment, large schools had the highest rate of AT services (92.1%) with nearly 18.5 times greater odds (odds ratio = 18.49 [95% CI = 16.20, 21.08]) versus small schools. The logistic model demonstrated that the odds of access to an AT increased by 2.883 times as the school size went up by 1 category. Conclusions: Nationally, suburban schools and large public schools had the greatest access to AT services compared with schools that were in more remote areas and with lower student enrollment. These findings elucidate the geographic locales and student enrollment levels with the highest prevalence of AT services. Ó by the National Athletic Trainers’ Association, Inc
1 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pubmed/33480996 ; https://pubmed.ncbi.nlm.nih.gov/33480996/ ; https://meridian.allenpress.com/jat/article/56/9/1010/451538/Athletic-Training-Employment-in-US-Secondary ; https://europepmc.org/article/MED/33480996
Keywords: adult; article; athletic trainer; athletics; controlled study; cross-sectional study; dept.hms; employment status; female; high school; human; male; outcome assessment; peer-reviewed; prediction; prevalence; training

Flu vaccinations: College campus not making the grade. A study of influenza vaccination at an urban public university. - Kreiger, Joan E; Zigmont, Victoria A.; Michalski, Carrie D; Borgognone, Kristen S (Journal of American college health : J of ACH, 2021)
Objective: Even healthy college students are vulnerable to severe complications associated with seasonal influenza (flu). Despite national directives to increase influenza vaccination compliance, college campuses remain woefully below national goals. This study aimed to identify factors correlated with the decision to voluntarily receive an influenza vaccine. Additionally, students’ reasons for non-vaccination were also examined. Participants: 1021 undergraduate students across four professional schools. Methods: A representative cross-sectional survey was conducted at a public, urban university. Results: The survey measured self-reported influenza vaccination: an overall influenza vaccination rate of 38% was identified. Student characteristics associated with increased influenza vaccination included students’ enrollment in academic health disciplines; being female; human papillomavirus (HPV) vaccination; and no marijuana use in the last month. Barriers to influenza vaccination included contraindications, mistrust issues, and personal reasons. Conclusion: Universities that can identify facilitators and barriers to voluntary influenza vaccination can assist with program initiatives to improve influenza vaccination compliance rates. © 2021 Taylor & Francis Group, LLC.
2 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34670106/
Keywords: dept.hms; dept.nur; dept.pch; peer-reviewed

Establishing a global standard for wearable devices in sport and exercise medicine: Perspectives from academic and industry stakeholders - Ash, Garrett I.; Stults-Kolehmainen, Matthew; Busa, Michael A.; Gaffey, Allison E.; Angeloudis, Konstantinos; Muniz-Pardos, Borja; Gregory, Robert; Huggins, Robert A.; Redeker, Nancy S.; Weinzimer, Stuart A.; Grieco, Lauren A.; Lyden, Kate; et al. (Sports medicine (Auckland, N.Z.), 2021)
Millions of consumer sport and fitness wearables (CSFWs) are used worldwide, and millions of datapoints are generated by each device. Moreover, these numbers are rapidly growing, and they contain a heterogeneity of devices, data types, and contexts for data collection. Companies and consumers would benefit from guiding standards on device quality and data formats. To address this growing need, we convened a virtual panel of industry and academic stakeholders, and this manuscript summarizes the outcomes of the discussion. Our objectives were to identify (1) key facilitators of and barriers to participation by CSFW manufacturers in guiding standards and (2) stakeholder priorities. The venues were the Yale Center for Biomedical Data Science Digital Health Monthly Seminar Series (62 participants) and the New England Chapter of the American College of Sports Medicine Annual Meeting (59 participants). In the discussion, stakeholders outlined both facilitators of (e.g., commercial return on investment in device quality, lucrative research partnerships, and transparent and multilevel evaluation of device quality) and barriers (e.g., competitive advantage conflict, lack of flexibility in previously developed devices) to participation in guiding standards. There was general agreement to adopt Keadle et al.’s standard pathway for testing devices (i.e., benchtop, laboratory, field-based, implementation) without consensus on the prioritization of these steps. Overall, there was enthusiasm not to add prescriptive or regulatory steps, but instead create a networking hub that connects companies to consumers and researchers for flexible guidance navigating the heterogeneity, multi-tiered development, dynamicity, and nebulousness of the CSFW field. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
9 citations (Crossref) [2023-10-31] https://waseda.pure.elsevier.com/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://repository.up.ac.za/handle/2263/81930?show=full ; https://www.ncbi.nlm.nih.gov/pubmed/34468950 ; https://researchportal.northumbria.ac.uk/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://pubmed.ncbi.nlm.nih.gov/34468950/ ; https://link.springer.com/article/10.1007/s40279-021-01543-5
Keywords: Consensus; Exercise; Humans; Sports; Sports Medicine; United States; Wearable Electronic Devices; adult; article; consensus; consumer; data science; dept.hms; electronic device; exercise; female; human; human experiment; investment; major clinical study; male; sport; sports medicine

Tell Me What You See: An Arts-Based Health Education Program for Youth. - Edmondson, Bonnie (Health Promotion Practice, 2021)
A cross-sector collaboration among a community-based organization, a prison arts program, and state departments of Public Health, Education, and Correction was established to address critical health education prevention efforts for at-risk high school-aged youth. The Tell Me What You See initiative utilizes artwork and poetry created by incarcerated youth to promote sexually transmitted disease (STD), HIV, and hepatitis prevention with students in public high schools and juvenile justice facilities. This innovative intervention integrates functional health knowledge and skills-based education through an art-based interdisciplinary approach reaching various populations of youth in multiple settings across a state. Evaluation results indicated that the materials effectively engage youth and open up a critical dialogue among peers and adults by addressing the role personal behavior can have in the prevention of STDs, hepatitis, and HIV. Lessons learned and recommendations are provided., (C)2021Sage Publications
1 citations (Crossref) [2023-10-31] Place: (C)2021Sage Publications
Keywords: Adolescent; Adult; Child; Educational Status; HIV/AIDS; Health Education; Health Promotion; Humans; STDs; Schools; Sexually Transmitted Diseases; adolescent; adolescent health; adult; arts; arts in public health; arts-based education; behavior change; child; community organization; creative arts; dept.hms; educational status; health education; health promotion; hepatitis; human; incarcerated youth; juvenile justice; partnerships; peer-reviewed; public health; school; school health; sexually transmitted disease

Physical activity participation, flourishing and academic engagement in adolescents with obesity. - McCoy, Stephanie; Rupp, Kristie (Pediatric Obesity, 2021)
Background: Adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. However, it is unknown how participation in physical activity influences flourishing and academic engagement in adolescents with obesity. The current study examined engagement in varying levels of physical activity and the likelihood of flourishing and academic engagement in adolescents with obesity. Methods: Analyses included 26 764 adolescents, ages 10–17 years, from the parent-reported, combined 2016–2017 National Survey of Children's Health. Participants were grouped by physical activity levels (none, low, moderate, daily). Outcome variables included flourishing (finishing tasks, staying calm when faced with a challenge and showing interest in new things) and academic engagement (completing all required homework and caring about doing well in school). Logistic regression models, adjusted for age, sex, race, household income, highest level of education in the household, behavioural conduct problems and depression assessed the likelihood of each outcome comparing physical activity levels among adolescents with obesity. Results: Adolescents with obesity who participated in any amount of physical activity (low, moderate and daily) or sports had significantly greater likelihood of flourishing and academic engagement compared those that did not engage in any physical activity (p's ¡ 0.05). Conclusions: Participation in even low amounts of physical activity or participation in sports increases the likelihood of flourishing and academic engagement in adolescents with obesity, which expands on previous findings that adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. © 2021 World Obesity Federation
5 citations (Crossref) [2023-10-31] Place: (C) 2021 International Association for the Study of Obesity
Keywords: Adolescent; Child; Exercise; Health Status; Humans; Pediatric Obesity; Schools; adolescence; adolescent; child; childhood obesity; dept.hms; exercise; flourishing; health status; human; obesity; peer-reviewed; physical activity; school

A PEP grant’s influence on change in a school district: One year post funding - Egan, Cate A.; Abel-Berei, Catherine P.; Karp, Grace Goc (Evaluation and program planning, 2021)
This study examined teachers' and administrators' perceptions of the institutionalization phase of the Carol M. White Physical Education for Progress (PEP) grant. A qualitative exploratory single case study (Yin, 2014) was utilized to examine the elements of the PEP grant that sustained or did not sustain after its conclusion, along with elements that were institutionalized and influences on this process. The findings were represented in the following three themes: (a) positive shifts, (b) backsliding, and (c) new directions, each with their own subthemes. Positive shifts includes sub-themes: (a) philosophy, (b) instruction, assessment and curriculum, (c) collaboration, and (d) respect. Backsliding includes sub-themes: (a) wellness team functioning, (b) the loss of PD and collaboration time, and (c) reduced data collection. New directions includes sub-themes: (a) mastery learning, (b) during school physical activity, (c) stress, and (d) administrative support. The factors that were institutionalized were quality physical education leadership roles, change in teachers' philosophies that influenced their instruction and assessment, and garnered administrative support. These elements were embedded into the physical education program and the school so much so that principals now expect the same type of programming from any new hire. Copyright © 2021 Elsevier Ltd. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: administration; administrative personnel; article; curriculum; dept.hms; funding; health education; human; human experiment; institutional framework; institutionalization; leadership; learning; peer-reviewed; perception; philosophy; physical activity; physical education; physiological stress; primary education; single-case study; student; teacher; teaching

Current activities centered on healthy living and recommendations for the future: A position statement from the HL-PIVOT network - Arena, Ross; Myers, Jonathan; Kaminsky, Leonard A.; Williams, Mark A.; Sabbahi, Ahmad; Popovic, Dejana; Axtell, Robert S.; Faghy, Mark A.; Hills, Andrew P.; Olivares, Silvia Lizett Olivares; Lopez, Mildred; Pronk, Nicolaas P.; et al. (Current Problems in Cardiology, 2021)
We continue to increase our cognizance and recognition of the importance of healthy living (HL) behaviors and HL medicine (HLM) to prevent and treat chronic disease. The continually unfolding events precipitated by the coronavirus disease 2019 (COVID-19) pandemic have further highlighted the importance of HL behaviors, as indicated by the characteristics of those who have been hospitalized and died from this viral infection. There has already been recognition that leading a healthy lifestyle, prior to the COVID-19 pandemic, may have a substantial protective effect in those who become infected with the virus. Now more than ever, HL behaviors and HLM are essential and must be promoted with a renewed vigor across the globe. In response to the rapidly evolving world since the beginning of the COVID-19 pandemic, and the clear need to change lifestyle behaviors to promote human resilience and quality of life, the HL for Pandemic Event Protection (HL-PIVOT) network was established. The 4 major areas of focus for the network are: (1) knowledge discovery and dissemination; (2) education; (3) policy; (4) implementation. This HL-PIVOT network position statement provides a current synopsis of the major focus areas of the network, including leading research in the field of HL behaviors and HLM, examples of best practices in education, policy, and implementation, and recommendations for the future. © 2021 Elsevier Inc.
10 citations (Crossref) [2023-10-31] Type: Review tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103372602
Keywords: Biomedical Research; COVID-19; Cardiorespiratory Fitness; Chronic Disease; Diabetes Mellitus; Diet; Exercise; Health Education; Health Policy; Healthy; Healthy Lifestyle; Humans; Implementation Science; Information Dissemination; Obesity; Patient Education as Topic; Quality of Life; Review; Risk Reduction Behavior; SARS-CoV-2; Sedentary Behavior; Smoking Cessation; Type 2; body mass; cardiorespiratory fitness; chronic disease; coronavirus disease 2019; dept.hms; education; epidemiology; exercise; health; health behavior; health care personnel; health care planning; health care policy; health education; health promotion; healthy diet; healthy lifestyle; healthy living medicine; human; information dissemination; knowledge; knowledge discovery; law; lifestyle; medical research; medicine; non insulin dependent diabetes mellitus; nutrition; obesity; pandemic; patient education; peer-reviewed; physical activity; psychological resilience; quality of life; risk reduction; sedentary lifestyle; sleep; smoking cessation; syndemic; unhealthy lifestyle behavior

Stakeholders’ perspectives on the effects of a PEP grant on a district-wide CSPAP - Abel-Berei, Catherine P.; Karp, Grace Goc; Fennell, Marcis; Drake, Elisa M.; Olsen, Simon (Journal of Teaching in Physical Education, 2021)
A Comprehensive School Physical Activity Program (CSPAP) can help children be physically active for 60 min/day. Physical Education for Progress grants provided opportunities to improve physical education and physical activity programming. Purpose: This study explored stakeholders' perspectives on the effects of a Physical Education for Progress grant on a district-wide CSPAP. Method: Stakeholders included physical educators (n = 10; K-12), administrators (n = 6), and one superintendent. Individual, semistructured interviews were used to examine how the grant affected stakeholders' perspectives of the CSPAP. Results: The grant affected the CSPAP by providing (a) opportunities for professional development, (b) opportunities to establish a K-12 curriculum map, and (c) access to equipment and resources. Discussion: Framed in social ecological theory, intrapersonal, interpersonal, institutional, and community levels were influenced by the grant. Interactions between levels enabled changes in all CSPAP components, especially quality PE. Conclusion: A Physical Education for Progress grant is a successful mechanism to enhance a district-wide CSPAP. © 2021 Human Kinetics, Inc.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85099226945
Keywords: dept.hms; peer-reviewed

Establishing a global standard for wearable devices in sport and fitness: Perspectives from the new england chapter of the american college of sports medicine members. - Ash, Garrett I.; Stults-Kolehmainen, Matthew A.; Busa, Michael A.; Gregory, Robert; Garber, Carol Ewing; Liu, Jason; Gerstein, Mark; Casajús, José A.; González-Agüero, A.; Constantinou, Demitri; Geistlinger, Michael; Guppy, Fergus M.; et al. (Current sports medicine reports, 2020)
The recent explosion of wearable technology and the associated concerns prompted the International Federation of Sports Medicine (FIMS) to create a quality assurance standard for wearable devices, which provides commissioned testing of marketing claims and endorsement of commercial wearables that test favorably. An open forum as announced in the conference advertising was held at the Annual Meeting of the New England Regional Chapter of the American College of Sports Medicine (NEACSM) November 7 to 8, 2019, in Providence, Rhode Island, USA for attending NEACSM members to voice their input on the process. Herein, we report the proceedings. The round table participants perceived the quality assurance standard to be important, but identified some practical process challenges that included the broad scope and complexity of the device universe, the need for a multiphase testing pathway, and the associated fees for product evaluation. The participants also supported the evaluation of device data analysis, behavioral influences, and user experience in the overall evaluation. Looking forward, the FIMS quality assurance standard faces the challenge of balancing these broader perspectives with practical constraints of budget, facilities, time, and human resources. © 2020 by the American College of Sports Medicine.
14 citations (Crossref) [2023-10-31] tex.ids: ashEstablishingGlobalStandard2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85079081076 type: Article
Keywords: Fitness Trackers; Humans; New England; Sports; Sports Medicine; United States; Wearable Electronic Devices; activity tracker; adult; article; budget; cosmos; data analysis; dept.hms; electronic device; human; peer-reviewed; quality control; sport; sports medicine

Promoting healthy ageing through light volleyball intervention in Hong Kong: study protocol for a randomised controlled trial - Leung, Ka Man; Chung, Pak-Kwong; Chan, Aileen W. K.; Ransdell, Lynda; Siu, Parco Ming Fai; Sun, Ping; Yang, Jinjin; Chen, Tie Cheng (Bmc Sports Science Medicine and Rehabilitation, 2020)
Background: Our pilot study has demonstrated improvements in health outcomes through participation in a new sport, light volleyball (LVB), among older adults. In response to the promising results of the LVB pilot study and the priority of allocating resources to the prevention of age-related fitness degradation by the Hong Kong (HKG) government, the present study aims to investigate the effectiveness of a LVB intervention on physical and psychological health attributes among older adults at a larger scale in HKG. Methods/design: This study will apply both quantitative and qualitative methods with a large sample (approximately 315 participants). We will adopt a randomized controlled trial (RCT) design to further evaluate the effectiveness of a LVB intervention on health outcomes against a comparison group, Tai Chi (TC), and a control group (C). Older adults will be eligible to join the intervention if they are (a) aged 65 years and above; (b) living in the community independently; (c) absent of diagnosed cognitive impairment; (d) not regular participants in a structured PA program for two years preceding the study; and (e) able to achieve a passing score on the Timed-up-and-go test (TUG) and Abbreviated Mental Test (AMT). About 315 participants will be randomly assigned into 3 groups in 1:1:1 ratio. LVB group participants will receive 16-week LVB program; TC group will utilize a simplified 24-form Yang Style TC, and C group participants will be instructed to maintain their normal daily activity and join regular non-exercise social gatherings. Measurements will be collected before and after the intervention, and 6 months and 12 months after completion of the intervention. Discussion: This intervention, if effective, will enhance older adult's physical and psychological health, and provide the data and evidence to support policymaking in relation to future PA promotion for older adults. Trial registration number: ChiCTR1900026657. © 2020 The Author(s).
5 citations (Crossref) [2023-10-31] WOS:000521410100001
Keywords: Adapted sport; Age-related fitness degradation; Ageing; Article; Hong Kong; Physical activity; Tai Chi; aged; clinical effectiveness; clinical trial protocol; cognitive defect; controlled study; dept.hms; healthy aging; human; major clinical study; mental health; mental test; peer-reviewed; physical activity; qualitative research; quantitative study; randomized controlled trial; timed up and go test; volleyball

Differences in health behaviors related to overweight/obesity by race/ethnicity in a diverse urban commuter college - Rupp, Kristie; Schnoll, Roseanne; Zigmont, Victoria A. (Journal of American College Health, 2020)
Objective: To examine health behaviors associated with overweight/obesity by race/ethnicity at a diverse urban college. Participants: 270 undergraduates (77.0% female; 26.7% non-Hispanic white) and median body mass index (BMI) of 23.1 kg/m2. Methods: A questionnaire about health-related behaviors as part of the “Get Fruved” project was used to measure health behaviors (sugar sweetened beverage (SSB), fruit and vegetable consumption, physical activity, stress, and sleep) by race/ethnicity. Multivariable logistic regression was used to assess the adjusted odds of engaging in positive health-related behaviors. Results: Non-Hispanic black and Hispanic students were 64% and 59% less likely to consume lower amounts of SSB. Hispanic students were 83% and 81% less likely to meet vegetable and fruit recommendations. Non-Hispanic black and other (including biracial) had reduced odds of meeting vegetable recommendations (AOR = 0.18 and 0.28). Conclusions: Disparities in SSB, fruit, and vegetable consumption represent potential intervention targets to improve health behaviors among racial/ethnic minorities. © 2020 Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31] WOS:000569184800001
Keywords: College; dept.hms; dept.pch; health behavior; peer-reviewed; race/ethnicity

The association between sympatho-vagal balance and central blood pressures - Latchman, P. L.; Gates, G.; Pereira, J.; Axtell, R. R.; Gardner, K.; Schlie, J.; Yang, Q.; Yue, T.; Morin-Viall, A.; Demeersman, R. (Physiology International, 2020)
Purpose: High central blood pressure is more predictive of cardiovascular disease (CVD) versus high peripheral blood pressure. Measures of central pressures (CPs) include, central systolic blood pressure (CSBP) and central diastolic blood pressure. Measures of central pressures augmentation (CPsA) include augmentation pressure (AP) and the augmentation index @ 75 beats$min-1 (AIx@75). Increased sympathetic tone (ST) is also associated with CVD. The low to high frequency ratio (LF/HF) is often used to determine sympatho-vagal balance. Given the association between ST, CPs, CPsA and CVD there is a need to understand the association between these predictors of CVD. The aims of this study were to examine the association between the LF/HF ratio, CPs, and CPsA in men and women collectively and based on gender. Methods: We measured the LF/HF ratio, CSBP, AP, and AIx@75 in 102 participants (41F/61M). The LF/ HF ratio was determined via power spectral density analysis. CSBP, AP, and AIx@75 were determined via applanation tonometry. Results: The LF/HF ratio was inversely associated with AP (r 5 -0.26) and AIx @75 (r 5 -0.29) in the combined group of men and women. The LF/HF ratio was inversely associated with CSBP (r 5 -0.27), AP (r 5 -0.28), and AIx@75 (r 5 -0.32) in men, but not in women. Conclusion: There is an inverse association between the LF/HF ratio, AP, and AIx@75 in men and women combined. The association between the LF/HF ratio, CSBP, AP, and AIx@75, differs based on gender. © 2020 Akademiai Kiado, Budapest.
1 citations (Crossref) [2023-10-31] WOS:000530051200014
Keywords: Adult; Arterial Pressure; Article; Augmentation index; Augmentation pressure; Blood Pressure; Cardiovascular System; Central diastolic blood pressure; Central systolic blood pressure; Electrocardiography; Female; Heart Rate; Humans; Male; Sex Characteristics; Sympathetic Nervous System; Sympatho-vagal balance; Vagus Nerve; Young Adult; adrenergic system; adult; arterial pressure; augmentation index; augmentation pressure; blood pressure; blood pressure measurement; cardiovascular disease; cardiovascular parameters; cardiovascular system; central pressures augmentation; dept.hms; diagnostic imaging; diastolic blood pressure; electrocardiography; female; gender; heart rate; human; low to high frequency ratio; major clinical study; male; pathophysiology; peer-reviewed; physiology; power spectrum; procedures; sexual characteristics; spectroscopy; sphygmomanometry; sympathetic tone; sympatho vagal balance; systolic blood pressure; tonometry; vagus nerve; young adult

Dimensions of burn survivor distress and its impact on hospital length of stay: A national institute on disability, independent living, and rehabilitation research burn model system study. - O'Brien, Kyle H (Burns : journal of the International Society for Burn Injuries, 2020)
OBJECTIVE: Guided by the Transactional Model of Stress and Coping, this study seeks to (1) examine the independent relationships between the level of distress among burn survivors, pre-morbid psychiatric history, and burn severity on length of hospital stay, and (2) to examine the relationship between having a premorbid psychiatric history and level of distress following a burn injury., METHODS: Data collected by the National Institute on Disability, Independent Living, Rehabilitation Research funded Burn Model System (N = 846) was used to theoretically link psychological distress with the length of hospital stay for survivors of burn injuries. Structural Equation Modeling was used to evaluate the aims of this study., RESULTS: Although counterintuitive, and while significant, burn severity was found to have a rather modest association with a burn survivor's level of distress, indicating that one's ability to cope may be a better predictor of distress rather than burn severity alone. Premorbid psychiatric history was significantly associated with increased levels of distress. While burn severity was associated with length of stay, level of distress did not act as a partial mediator. Length of stay was, however, significantly related to having a premorbid-psychiatric history. Of notable interest, a significant racial, ethnic, and gender difference exists in level of distress. Women and people of color experience higher levels of distress holding constant burn severity and psychiatric history., CONCLUSION: A need exists to assess for and address premorbid and current mental health challenges of burn survivors, specifically the ability to cope, especially among people of color and women, regardless of the burn size or severity. Copyright © 2019 Elsevier Ltd and ISBI. All rights reserved.
1 citations (Crossref) [2023-10-31] Place: Netherlands O'Brien, Kyle H. Southern Connecticut State University, School of Health and Human Services, Department of Social Work, Department of Health and Movement Sciences, 101 Farnham Avenue New Haven, CT 06515, United States. Electronic address: obrienk9@southernct.edu.
Keywords: *Adaptation; Psychological; *Burns/px [Psychology]; *Length of Stay/sn [Statistics & Numerical Data]; *Mental Disorders/px [Psychology]; *Psychological Distress; *Stress; Psychological/px [Psychology]; Adaptation; Psychological; Adolescent; Adult; African American; African Americans; African Americans/px [Psychology]; African Americans/sn [Statistics & Numerical Data]; Aged; Aged; 80 and over; Article; Body Surface Area; Burn survivors; Burns; Burns/ep [Epidemiology]; Burns/pa [Pathology]; Burns/pp [Physiopathology]; Caucasian; Distress; Ethnic Groups; European Continental Ancestry Group; European Continental Ancestry Group/px [Psychology]; European Continental Ancestry Group/sn [Statistics & Numerical Data]; Female; Hispanic; Hispanic Americans; Hispanic Americans/px [Psychology]; Hispanic Americans/sn [Statistics & Numerical Data]; Humans; Integrated care; Latent Class Analysis; Length of Stay; Length of stay; Male; Mental Disorders; Mental Disorders/ep [Epidemiology]; Mental health; Middle Aged; Models; Psychological; Psychological Distress; Psychosomatic; Sex Factors; Stress; Psychological; Stress; Psychological/eh [Ethnology]; Stress; Psychological/ep [Epidemiology]; Survivors; Young Adult; adolescent; adult; aged; body surface; burn; burn survivor; coping behavior; dept.hls; dept.hms; dept.rec; distress syndrome; electric burn; ethnic group; ethnology; female; hospital discharge; hospitalization; human; latent class analysis; length of stay; major clinical study; male; mental disease; mental stress; middle aged; outcome assessment; pain severity; pathology; pathophysiology; peer-reviewed; personal experience; psychiatric treatment; psychological aspect; psychological model; psychology; scald; secondary analysis; sex factor; structural equation modeling; survivor